Four-layer folding framework: design, GAP synthesis, and aggregation-induced emission - Zhang, Sai; Chen, Daixiang; Wang, Jia-Yin; Yan, Shenghu; Li, Guigen (Frontiers in Chemistry, 2023)
The design and synthesis of a type of [1+4+2] four-layer framework have been conducted by taking advantage of Suzuki-Miyaura cross coupling and group-assisted purification (GAP) chemistry. The optimized coupling of double-layer diboronic esters with 1-bromo-naphth-2-yl phosphine oxides resulted in a series of multilayer folding targets showing a broad scope of substrates and moderate to excellent yields. The final products were purified by GAP chemistry/technology simply by washing crude products with 95% EtOH without the use of chromatography and recrystallization. The structures were fully characterized and assigned by performing X-ray crystallographic analysis. UVvis, photoluminescence (PL) and aggregation-induced emission (AIE) were studied for the resulting multilayer folding products.